Handbook for attention deficit hyperactivity disorder in adults. - Kings College London (Springer Healthcare Ltd., 2013)
This book is a direct response to a severe treatment gap in recognising, treating and managing attention deficit hyperactivity disorder (ADHD) in adults. Affecting 3-4% of the global population, ADHD has long been considered a pediatric psychiatric condition and continues to be overlooked in adults, who often go on to endure a lifetime of clinically significant impairments that affect work performance, social behavior, and personal relationships. However, in the wake of the recognition of ADHD in adults in the Diagnostic and Statistical Manual of Mental Disorders IV (considered the absolute gold standard in psychiatry) and a greater number of pharmaceutical treatments being indicated for adults, this book will increase awareness of the condition and advocate expanding ADHD treatment across all age ranges. The book is especially relevant to psychiatrists, GPs, and specialist psychiatric nurses , while also a useful resource for patient societies and advocacy groups.